Advanced control strategy of DFIG during symmetrical grid fault - Tariq Riouch; Cristian Nichita (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
This article proposes a novel scheme to improve the doubly-fed induction generator (DFIG) behavior during grid fault. The DFIG’s are sensitives to voltage variations when abrupt variations of the wind velocity arrive. For enhancing DFIG behavior, protecting the converters, and smoothing the fluctuations power output of the DFIG under sag voltage; a novel hybrid energy storage system scheme and its controller are proposed. The main advantages of our approach are a faster response and suppressing overvoltage on DC bus and globally less stress in the storage system. The control structure decreases the tiredness on the battery and restores the DC bus voltage rapidly, globally the battery system operating time increases. The results obtained by simulations in MATLAB validate the benefits of the suggested control.